Stock option taxation: A missing piece in European innovation policy? - Magnus Henrekson; Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2017)
Venture capital has become a dominant form of innovation finance, used by many high-tech startups. Europe lags the U.S. in both VC activity and the creation of successful startups, and has recently been surpassed by China. Few European countries have rates of VC activity commensurable to their deep finan-cial markets, strong legal institutions and high R&D spending. This paper points to the tax treatment of employee stock options as an important and neglected explanation. Innovative entrepreneurship is a complex activity that normally requires support structures and collaboration by actors providing financial and human capital to startups. As a response to high uncertainty and transaction costs, VC financiers developed a model where founders and key recruitments are compensated with stock options under complex contracts. While most countries tax stock options as labor earnings, the U.S. allow them to be taxed at a low capital gains tax rate. This has led to near universal use of stock options in U.S. VC deals, while this remains less common in Europe. There is a strong correlation between favorable tax treatment of employee stock options and VC activity. We discuss the interaction between tax policy and contract theory to show why employee stock options are a suitable solution to agency and incentive problems in this sector. A major advantage of this tax policy is that it narrowly targets entrepreneurial startups without requiring broad tax cuts.
Keywords: L26; H25; H3; K34; 330; Business taxation; Corporate governance; Entrepreneurship; Innovation; Institutions; Tax policy; Stock options; Venture capital